Approval and implementation of the “National Technical Guideline for Standardization of the Pregnant Woman Integral Care for Voluntary Interruption of less than 22 weeks Pregnancy for Therapeutic Reasons with Informed Consent within the context of Article - Aspilcueta Gho, Daniel (2015)
Abortion for medical health reasons is not penalized by the Peruvian Penal Code 1924. This norm has not been applied as Clinical Practice Guidelines or Regulations are lacking. The basic conditions include abortion should be performed by a physician, when it is the only way to save a pregnant woman’s life or to prevent serious and permanent complications, and with consent from the woman or from his legal representative. There is a series of documents that Peru has subscribed in matters of human rights that compromise implementation of legal abortion service: the Convention on Elimination of all Forms of Discrimination against Women, CEDAW; the Cairo Conference Action Program (CIPD), the Beijing Conference on Women. The Peruvian Ministry of Health approved the “National Technical Practice Guideline for Standardization of the Pregnant Woman Integral Care for Voluntary Interruption of less than 22 weeks Pregnancy for Therapeutic Reasons with Informed Consent within the context of Article 119th of the Penal Code”, published on June 28, 2014. The provision for abortion services in the public health system is a challenge. Many hospitals are overloaded and have limitations to services access; adequately trained personnel, supplies, equipments and willingness are required. Challenges include sensitizing and recognizing the woman as a citizen with rights, wide diffusion in health establishments and services, training to assure informed consent and procedure quality including appropriate use of manual vacuum aspiration and misoprostol.